21 LESSONS FOR THE 21st CENTURY - YUVAL NOAH HARARI (LONDON JONATHAN CAPE, 2018)
Shares insights into such present-day issues as the role of technology in transforming humanity, the epidemic of false news, and the modern relevance of nations and religion.
Keywords: TECHNOLOGY; WORLD POLITICS; MODERN CIVILIZATION